Surgical team development and clinical application of transanal total mesorectal excision - Tian Tian; Liu Dingsheng; Zhang Hong (结直肠肛门外科)
The safety and efficiency of transanal total mesorectal excision (taTME) in clinical practice are critical concerns for surgical teams, particularly those in the early stages of adopting this technique. Based on the clinical practice experience of over 230 cases of taTME at our center, we propose recommendations on surgical team development and clinical application of this technique to provide clinical references for enhancing surgical safety. Meanwhile, we share our center’s practical experiences and technical training insights with fellow professionals and hope to contribute to the broader adoption of taTME.